Heavy metal leaching of solidified sludge from a glass components industry - Yaziz, M.I.; Chin, F.L.; Tang, S.N.; Bich, N.N. (Marcel Dekker IncNew York, 1999)
Leaching tests conducted on raw sludge wastes from a glass components manufacturing factory using the US EPA TCLP procedure showed that Pb, Hg, As and Ba leached at pH<3.5 whilst Cd and Cr did not. To control the leaching, asphalt, a mixture of asphalt and powdered activated carbon (PAC) and Portland cement were used as fixing agents to stabilize the sludge. Leaching tests on the stabilized sludge using leachants of pH 2.5-7.0 showed that the lowest leachate metal concentration were obtained from the sludge which had been stabilized using a mixture of asphalt and PAC. Portland cement at a cement-to-sludge ratio of 0.5 also reduced the leaching of metals from the solidified sludge with metals concentrations in the leachate lower than the US EPA regulatory limits.; Leaching tests conducted on raw sludge wastes from a glass components manufacturing factory using the US EPA TCLP procedure showed that Pb, Hg, As and Ba leached at pH<3.5 whilst Cd and Cr did not. To control the leaching, asphalt, a mixture of asphalt and powdered activated carbon (PAC) and Portland cement were used as fixing agents to stabilize the sludge. Leaching tests on the stabilized sludge using leachants of pH 2.5-7.0 showed that the lowest leachate metal concentration were obtained from the sludge which had been stabilized using a mixture of asphalt and PAC. Portland cement at a cement-to-sludge ratio of 0.5 also reduced the leaching of metals from the solidified sludge with metals concentrations in the leachate lower than the US EPA regulatory limits.